(untitled) (Colección, 2017)
Between late August 1943 and September 1945, many opponents of the military regime in Argentina had to refugee in Montevideo. They were prominent members of different political parties united by a strong rejection and condemnation of Argentina´s current authoritarian political regime. During their exile, they published Voz Argentina and Pueblo Argentino and organized a prolific political activity through two organizations, Patria Libre and Asociación de Mayo. While the main enemies of the military government who were exiled developed a lot of significant political and cultural activities in Montevideo, the historiography has not paid attention to their experience. This paper presents a preliminary inquiry of this political exile in Uruguay. In particular, its specific objective is to analyze Luciano Molinas, Nicolás Repetto, Santiago Nudelman and José Aguirre Cámara thoughts, focusing on two themes: how these actors perceived themselves as opponents of a military regime and how they conceptualized the main political events taking place in their country.